The role of R-loops in the pathology of trinucleotide expansion diseases - Groh, M (2015)
Friedreich ataxia and fragile X syndrome are among 40 human diseases associated with expansion of repeated DNA sequences. In both disorders repeat expansion leads to gene silencing, the molecular mechanism of which is not well understood. It was proposed that formation of unusual DNA structures such as R-loops over repeat regions may play a role, but their molecular function has not been investigated in vivo. R-loops are three-stranded structures, which occur when RNA hybridises to a complementary DNA strand. This leads to formation of an RNA/DNA hybrid and results in displacement of the other DNA strand. In the first part of this thesis, I show that RNA/DNA hybrids are formed in patient cells on expanded repeats of FXN and FMR1 genes, mutated in Friedreich ataxia and fragile X syndrome. These RNA/DNA hybrids are stable, colocalise with repressive chromatin marks and impede FXN gene transcription in patient cells. Furthermore, I studied the relationship between repressive chromatin and RNA/DNA hybrids. I found that increasing RNA/DNA hybrid levels triggers heterochromatin formation and leads to transcriptional repression of the FXN gene, providing a direct molecular link between RNA/DNA hybrids and the pathology of expansion diseases. The current understanding of R-loop biology in health and disease is limited by the small number of proteins known to bind RNA/DNA hybrids or R-loops in vivo. In the second part of this thesis I therefore established an affinity purification approach, employing the RNA/DNA hybrid-specific S9.6 antibody followed by mass spectrometry to identify RNA/DNA hybrid-binding proteins in HeLa cells. Using this approach, 469 proteins were identified that constitute the RNA/DNA hybrid interactome by stringent biochemical and statistical criteria. Identified proteins include known R-loop factors senataxin, SRSF1 and topoisomerase I and yet uncharacterised interactors, such as RNA- and DNA-binding proteins, DNA repair and chromatin factors, and helicases. To demonstrate the biological relevance of the RNA/DNA hybrid interactome, I show that the top candidate DHX9 helicase promotes RNA/DNA hybrid resolution in vivo. Furthermore, DHX9 and other RNA/DNA hybrid interactome helicases are overexpressed in cancer, revealing a strong link between R-loop-mediated genome instability and human disease.